Television as a Symbolic Culture: A Study of Media Ethnography in Bogor - Dinda Silvia Izdihar Fairuz; Khairunnisa Meydina; Syahya Rembulan (COMMENTATE: Journal of Communication Management, 2022)
Television has become a part of everyday life for people in the world. Television is an electronic mass media that is greatly enjoyed by the public. This media has become part of everyday life for the community, besides that television also has a great influence on attitudes and behavior for its audience, which has positive and negative effects. The program presented by television is a program that can provide quick information for the audience. This journal aims to analyze the meaning of television construction given by the people of Ciluar Village, Bogor. The role of television as a source of information and a means of entertainment has developed into a cultural symbol in a society. Television shifted to become a cultural symbol between a society. This study uses a qualitative approach with ethnographic media. The data collection technique used is observation with three informants involved in this interview, because they meet the criteria (requirements). This study uses selective coding to classify several findings that can describe how the people of Ciluar Village apply television as their symbolic culture. Based on the results of the interview, there are three selective coding, namely interest, watching habit, and television as a symbolic culture. The results show that television has a high influence on measuring the level of equality, especially class and social status, as well as being a source of information and can be a means of entertainment. The people of Ciluar Village, Bogor interpret television according to their socio-cultural context. For those in Ciluar Village, television can be a source of information and as a means of entertainment.